Las tecnologías de la información y la comunicación utilizadas por los docentes de matemáticas en el bloque curricular números y funciones y su incidencia en el desarrollo de destrezas con criterio de desempeño en los estudiantes de primer año de bachillerato del colegio nacional Adolfo Valarezo, de la ciudad de Loja, periodo académico 2013-2014. Lineamientos alternativos - Jiménez Gaona, Romel Leonardo (2015)
This investigative work makes reference to the subject: COMMUNICATION AND INFORMATION TECHNOLOGIES USED BY TEACHERS OF MATHEMATICS IN THE CURRICULUM BLOCK NUMBERS AND FUNCTIONS AND THEIR IMPACT ON THE DEVELOPMENT OF SKILLS WITH PERFORMANCE CRITERION IN FIRST YEAR OF BACHELOR'S DEGREE FROM THE NATIONAL HIGH SCHOOL ADOLFO VALAREZO OF LOJA CITY, ACADEMIC PERIOD 2013-2014, which was developed on the basis to the general objective: to end of the information and communication technologies used by teachers of mathematics in the curriculum's block of numbers and functions and their impact on the development of skills with performance criterion in the students of the first year of National High School Adolfo Valarezo of Loja city, academic period 2013-2014. The main methods used were the scientist, deductive, inductive, analytic and hypothetical deductive, that allowed to operate, studying and analyzing the theoretical and empirical data that influence the knowledge and use of ICT as a teaching resource for teachers; the main techniques used were the survey and the literature, in order to obtain basic information on the topic, this study was carried out to three teachers and 60 students from the first year of B.G.U. of the National High School Adolfo Valarezo. The results obtained are in full correspondence with the hypothetical approach formulated, demonstrating that, indeed, there is a significant incidence between the use of ICT in the classroom and the achievement of skills with performance criteria. This has been designed not only with the field information obtained, but with meticulous analysis of theoretical references that come from other researchers developed around the theme and which correspond to previously proven theories. This framework highlights results such as: that in the study of block curriculum numbers and functions of the first year of high school, you would get better learning outcomes, if teachers more used ICT to support teaching of the contents of the block numbers and functions. That teachers will simply not only use technology as the projector and the laptop and sometimes a program like the Internet or slides in Power Point for the exposure of the subjects to be treated, but to be trained in order to use the largest number of computer programs to boost classes and obtain better learning outcomes. The present search will be an important contribution for all teachers, especially those of the National High School Adolfo Valarezo, prestigious educational institution that has provided important contributions to education in the southern region of the country since the investigative scope.